Measuring the e-Learning Autonomy of Distance Education Students - Mehmet Firat (Open Praxis, 2016)
Previous studies have provided evidence that learner autonomy is an important factor in academic achievement. However, few studies have investigated the autonomy of distance education students in e-learning environments. The purpose of this study is to evaluate the e-learning autonomy of distance education students who are responsible for their own learning. For this purpose, as the first step of the study, an e-learning autonomy scale was developed. Analyses of the validity and reliability of the scale were carried out with the participation of 1,152 distance education students from Anadolu University, Open Education System. The scale has an internal consistency coefficient of á = 0.952 and a single factorial model that explains 66.58% of the total variance. The scale was implemented with 3,293 students from 42 different programs. According to the findings, student autonomy in e-learning environments is directly proportional to level of ICT use but not affected by program or gender.